2003
DOI: 10.1002/fuce.200332108
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Modules for Vehicles with a Fuel Cell Drive

Abstract: In spite of the high efficiency of fuel cell drives for vehicles, cooling is a key problem. The present article reveals the reasons for cooling limits and their physical causes. This leads to deductions about what kind of actions can be taken to increase cooling performance. The implementation of these measures is demonstrated by means of examples of cooling modules for vehicles with a fuel cell drive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…However, lower operating temperatures compared to IC engines require larger radiator frontal areas to achieve thermal balance. Fronk et al and Rogg et al [1,3] have both looked at novel radiator designs to try to minimise radiator sizes in fuel cell vehicles. Islam et al and Zakaria et al [22,23] investigated the potential of using nanofluids in the liquid coolant loop of PEM fuel cell stacks, Islam et al [22] claimed up to a 10% reduction in radiator frontal area from using a nanofluid compared to conventional water/ethylene glycol coolant mix.…”
Section: Liquid Coolingmentioning
confidence: 98%
“…However, lower operating temperatures compared to IC engines require larger radiator frontal areas to achieve thermal balance. Fronk et al and Rogg et al [1,3] have both looked at novel radiator designs to try to minimise radiator sizes in fuel cell vehicles. Islam et al and Zakaria et al [22,23] investigated the potential of using nanofluids in the liquid coolant loop of PEM fuel cell stacks, Islam et al [22] claimed up to a 10% reduction in radiator frontal area from using a nanofluid compared to conventional water/ethylene glycol coolant mix.…”
Section: Liquid Coolingmentioning
confidence: 98%
“…Furthermore, in liquid humidified systems the cathode exhaust stream must be cooled to extract water for maintaining membrane humidification. These factors combined require larger heat transfer areas and higher cooling loads than IC vehicles of comparative power, presenting packaging constraints and reducing efficiency [4]. A study by Ford Motor Company showed that for a fuel cell operating at 80-90°C pressurised to 3 atm requires 1.5 times the radiator frontal area and 2.5 times larger air flow than an IC powertrain of comparable power [5].…”
Section: Introductionmentioning
confidence: 98%
“…Yi and Nguyen [8] developed an advanced model to compare different fuel cell designs with co-flow and counter-flow heat exchangers. Rogg et al [9] presented the reasons for the cooling limits of fuel cells designed for vehicles. Zhang et al [10] reported a technique to model the thermal system of a PEFC stack, which estimated the fundamental thermalphysical behaviors of the thermal system.…”
Section: Introductionmentioning
confidence: 99%